MODEL PENGARUH TINGKAT SETENGAH PENGANGGURAN, PEKERJA INFORMAL DAN PENGELUARAN PERKAPITA DISESUAIKAN TERHADAP KEMISKINAN DI INDONESIA TAHUN 2015-2017 - Meimela, Aida (Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
Indonesia's poverty rate in the last five years has always decreased annually to 10,64 percent (2017). However, this pattern is not followed by all provinces in Indonesia. Some provinces experience fluctuations every year. Even in 2017, poverty has risen in some provinces. This condition is influenced by some factors of both labor and economy. From the existing literature, there is little research on the effects of underemployment rate, informal workers and adjusted per capita spending on poverty in Indonesia. Therefore, this research is very important to do. This study aims to model the underemployment rate, informal workers and per capita expenditure on poverty using the panel data regression analysis of the 2015-2017 period. The result of the research shows that the best model is Random Effect Model (REM). The rate of underemployment has a positive and significant impact on poverty (level of confident 90 percent). In addition, per capita expenditures have negative and significant impact on poverty. The results of the study show that the government is expected to pay more attention to the indicator of the underemployment rate, because this variable has a largest influence(o,04 percent) on poverty compared to all variables.Keywords : labor, panel regression, underemployment, poverty, random effect model